HUBUNGAN ANTARA TINGKAT RELIGIUSITAS DAN KEMATANGAN EMOSI DENGAN KECENDERUNGAN TERJADI KEKERASAN DALAM RUMAH TANGGA - Sillakhudin . (Universitas 17 Agustus 1945 Samarinda, 2013)
The research is based on many of family abuse in public. There are many factors of the agents, the proponent, and the controlling and the controls of family abuse. Some of them are the religious advance and emotional competence. The porpose of th research is to known the relationship between religious advance and emotional competence with tendency to family abuse. The research sample is 70 respondences include of officers and students of Tecnique Faculty of University 17 Agustus 1945 Samarinda. The respondences are men, married, the age from 25 years old up to 45 years old. The sampling by using purposive random sampling technique.The research datas is taken by using Hoyt technique and it found that there is significant negative relationship between religious advance and emotional competence with tendency of family abuse is R= 0,429 ; F = 7,552 with ab = 2/67 ; with opportunity P = 0,001 (P < 0,01) with effective contribution 2,238 % for religious advance and 9,487 % for emotional competence. From t test we found that there is the significant relationship between religious advance and emotional competence with tendency to family abuse.